Analysis of the Efficiency of China's Medical Service Resources under the Background of Hierarchical Medical Policy - Shaomin Wang; Qunshan Tao (Tehran University of Medical Sciences, 2021)
Background: Hierarchical medical system (HMS) is a good policy to promote the fairness of medical services for residents. Given the importance of HMS, it is necessary to know the implementation effect of the policy. Therefore, we aimed to analyze the efficiency of medical service resources in China under the background of hierarchical medical policy. Methods: Based on the panel data of China's medical resources in 2015-2019, we used DEA model to calculate the technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) of medical resources from both lateral and longitudinal aspects. We used Malmquist index to evaluate the change trend of efficiency, and further we compared the efficiency differences of regions and medical institutions. Results: In lateral evaluation results, TE was relatively stable, while total factor productivity (TFP) was on the rise. In longitudinal evaluation results, TE and TFP showed a downward trend. Conclusion: The government should consider the differences in development between regions and make health plans by regions. Medical institutions should strive to break down the constraints and make use of their advantages, which is conducive to improving efficiency.